Reactivation of herpes simplex virus type 2 from a quiescent state by human cytomegalovirus. - Colberg-Poley, A M (1979)
The ability of human cytomegalovirus to stimulate replication of herpes simplex virus type 2 (HSV-2) was examined. The system used involved HSV-2-infected human embryonic lung cells under conditions (39.5-40 degrees C) in which HSV-2 remains undetectable. Reactivation of HSV-2 was maximal and persisted for the longest duration when cultures were superinfected with 0.02 plaque-forming unit of human cytomegalovirus per cell. Infectious HSV-2 appeared 2 days after superinfection with human cytomegalovirus and ranged from 10(2) to 10(6) plaque-forming units per culture. Virus reactivated from these cultures was neutralized by rabbit immune serum produced against HSV-2. The specificity of this interaction was demonstrated by various criteria: production of HSV-2 was not observed in cultures treated with mock infecting fluid, and inactivation of human cytomegalovirus by heat, ultraviolet irradiation, or immune serum prior to superinfection eliminated its ability to induce HSV-2 replication. These results sugges that interaction between these two human herpesviruses may be of importance in herpesvirus latency in vivo.